Hereditary Orotic Aciduria and the Excretion of Orotidine - Nyhan, William L.; Gangoiti, Jon A. (Neuropediatrics, 2016)
Objective Orotic aciduria and deficiency of uridine monophosphate synthetase have been observed in a patient, studied over 10 years, who had no megaloblastic anemia. Excretion of orotic acid and orotidine were 8.24 and 0.52 mmol/mol of creatinine. The ratio of 15.85 differed appreciably from that of 6 patients reported with no megaloblastic anemia.Methods The analysis of orotidine by gas chromotography mass spectrometry was conducted.Conclusion Patients with orotic aciduria with and without megaloblastic anemia cannot be distinguished by ratio of orotic acid to orotidine.
Keywords: orotic aciduria; orotidine; megaloblastic anemia